Denaturalization and visibilization of ‘violence and discriminatory behavior’.: Scaling up devices to enable Comprehensive Sexuality Education (CSE). Open paths in the Faculty of Humanities, Arts and Social Sciences in Concepción del Uruguay (Universidad Autónoma de Entre Ríos, Argentina) (Itinerarios Educativos, 2020)
As a result of some classroom experiencesand evidenced gaps in the training plans of future teachers and graduates in relation to issues of gender /sexuality / rights, which are differentiated, transversaland compulsory contents according to Ley Nacionalde Educación 263206/06 (Argentine education actNr. 26.206/06), the Geography degree program ofthe Faculty of Humanities, Arts and Social Sciences(FHAYCS, for its Spanish initials) of Universidad Autónoma de Entre Ríos (UADER, for its Spanish initials)promoted the University Extension Sessions: ‘Denaturalization and visibilization of violence and discriminatorybehavior by scaling up devices to enable CSE and reflecton situations/problems we go through as a community’. These issues constitute compulsory contents tobe addressed at all levels of the education system, andthus the aforementioned act defines CSE spaces foreach stage of formal education. Educational and healthinstitutions have started an erratic way riddled withresistance that enables some work lines to implementCSE contents. These Sessions, which were declaredof Institutional Interest according to Res. CD FHAYCS/UADER 1549/18, included 4 Workshops specificallyrelated to an interdisciplinary health/education perspective based on the CSE act, discrimination and respectfor diversity, violation of rights in educational contexts,and views on body through art, clothing, and socialtrends. The meetings that were intended to representa contribution to the treatment of these issues in theuniversity field were closed with collective artistic productions and a photographic exhibition linked to theaddressed issues.
Keywords: cse; gender; rights; visibilization; diversity